Consumer preference for infant milk‐based formula with select food safety information attributes: Evidence from a choice experiment in China. (27th July 2018) - Yin, Shijiu; Lv, Shanshan; Chen, Yusheng; Wu, Linhai; Chen, Mo; Yan, Jiang
Abstract: The melamine milk powder incident in China undermined consumers' confidence in dairy products including infant milk‐based formula (IMF). In this study, three quality IMF product attributes are considered in a choice experiment survey in China including organic label, traceability information, and country of origin (COO). Results reveal that consumers have the highest willingness to pay (WTP) for an organic label from the United States. Traceability information regarding milk production was preferred the most. Consumers prefer IMF originated from the United States and New Zealand over China. Consumer heterogeneity was revealed through a latent class model. Compared to price‐sensitive consumers, certification‐inclined consumers had significantly higher WTP for organic labels. Origin‐preferred consumers displayed higher WTP for IMF produced in the United States and New Zealand, and concerned consumers had higher WTP for all food safety informational attributes. The conclusions of this paper should not only aid Chinese domestic producers and policy makers, they should also provide references for organic certification bodies and dairy enterprises from around the world for their business decision making.